Students’ Reading Competency on High Order Thinking Items in The Junior High Schools - Riadi, I. K. Sutra; Tantra, D. K. (Journal of Education Reseach and Evaluation, 2020)
The aimed of this study was to describe and compare the students’ reading competency in answering high order thinking items across classes, text genres, and reading indicators. In the present study, critical reading is defined as reading for comprehension of high-order-thinking items which are focused on the four indicators of reading competency, namely: main idea, specific ideas, textual references, and word meanings. This research was conducted quantitatively and focus on year seven students. To reach such purpose, a purposive sampling technique was used to choose the sample. The subjects of this study were 238 students. The instruments used to collect the data was a Reading Competency Test. The collected data were analysed quantitatively and interpreted descriptively. The first finding of this research shows that the level of the students’ reading competency in answering high order thinking items are categorized weak or low level on both the descriptive texts and recount texts which is the descriptive text and finding main idea are the highest mean score. The second finding shows that there is no significant difference of students’ reading competency in answering high order thinking items across classes, text genres, and reading indicators which is analysed by using One Way ANOVA with significant score is 0.054. > 0.05, thus Ho is accepted and H1 is rejected. The result of the study is an important information about the students’ reading competency in answering HOTS items. it is necessary to do next research in order to design future effective educational strategy or educational policy in learning.